**stumped by this problem ("expansion of products"): given (x+b)(x-1)=x2+3x-4, find "b"**

Question is find the value of 'b' in the equation: (x+b)(x-1)=x

^{2}+3x-4

I reduced the equation as follows:

- x
^{2}-x+bx-b=x^{2}+3x-4 - x
^{2}-x+bx-b=x^{2}+3x-4 - bx-b=2x-4

The answer key says that it is 4, as does wolfram alpha - but neither offer a step by step solution.

I am just starting with maths as an adult in order to rewrite my High School levels. I never took it past the early years of high school and not till the end.

Would appreciate a hint as to where to read up, or what the name of the problem is...

Thanks